2013
DOI: 10.1371/journal.pgen.1003193
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolism and Development Is Mediated by LlmF Control of VeA Subcellular Localization in Aspergillus nidulans

Abstract: Secondary metabolism and development are linked in Aspergillus through the conserved regulatory velvet complex composed of VeA, VelB, and LaeA. The founding member of the velvet complex, VeA, shuttles between the cytoplasm and nucleus in response to alterations in light. Here we describe a new interaction partner of VeA identified through a reverse genetics screen looking for LaeA-like methyltransferases in Aspergillus nidulans. One of the putative LaeA-like methyltransferases identified, LlmF, is a negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 58 publications
4
84
0
Order By: Relevance
“…Such a function has been supported by the loss of LaeA function in vivo in a double mutation in motif I (23). Furthermore, it has been shown that LaeA can bind AdoMet in vitro (31). These data all suggest that LaeA could be a bona fide methyltransferase.…”
Section: Laeamentioning
confidence: 77%
See 2 more Smart Citations
“…Such a function has been supported by the loss of LaeA function in vivo in a double mutation in motif I (23). Furthermore, it has been shown that LaeA can bind AdoMet in vitro (31). These data all suggest that LaeA could be a bona fide methyltransferase.…”
Section: Laeamentioning
confidence: 77%
“…Strains harboring a single integration of the complementation vector at the pyroA locus were subsequently crossed to RJW130.1 (pyroA4 and ⌬laeA) and/or RJMP260.28 (pyroA4, hhoA-mCherry, and ⌬laeA) to generate prototrophic strains. Analysis of sterigmatocystin production was done from point-inoculated cultures grown for 4 days in dark and light conditions, and sterigmatocystin was extracted and visualized via thin layer chromatography (31). Analysis of asexual and sexual sporulation was conducted as described previously (34) with the minor modification of using Champe's media for sexual developmental induction (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of LaeA results directly or indirectly in increased repressive trimethylation marks at histone 3 in A. nidulans (372) or Trichoderma atroviride (373). VeA is a hub for several interacting methyltransferases, including LaeA, VipC/LlmB, VapB, or LlmF in A. nidulans or P. chrysogenum (374)(375)(376). The A. nidulans VipC-VapB methyltransferase heterodimer acts as negative regulator of sexual development and as a positive regulator of asexual development and is part of an epigenetic methyltransferase signal transduction pathway.…”
Section: Fruiting Body Formationmentioning
confidence: 99%
“…Once assembled in the nucleus of A. nidulans, the velvet complex drives sexual development and production of SMs, whereas these processes are repressed under illuminating conditions resulting from a dissociated velvet complex [81]. Consequently, when localization of members of this complex is compromised, such as with VeA via interacting with the newly described LaeA-like methyltransferase LlmF, neither sexual development nor SM production can proceed normally [98]. The LlmF mechanism of VeA control appears conserved in other ascomycetes as well [99].…”
Section: Velvet Complex-lightmentioning
confidence: 99%